Animals & Ethics 101 Thinking Critically About Animal Rights - Nobis, Nathan (Open textbook library., 2018)
This book provides an overview of the current debates about the nature and extent of our moral obligations to animals. Which, if any, uses of animals are morally wrong, which are morally permissible (i.e., not wrong) and why? What, if any, moral obligations do we, individually and as a society (and a global community), have towards animals and why? How should animals be treated? Why? We will explore the most influential and most developed answers to these questions – given by philosophers, scientists, and animal advocates and their critics – to try to determine which positions are supported by the best moral reasons.